ChemInform Abstract: Polyketides from the Mangrove‐Derived Fungal Endophyte Pestalotiopsis clavispora. Issue 34 (4th August 2016) - Perez Hemphill, Catalina Francis; Daletos, Georgios; Liu, Zhen; Lin, Wenhan; Proksch, Peter
Abstract: Pestalpolyol I (I), pestapyrones A (IIa) and B (IIb), (R)‐periplanetin D (III), pestaxanthone (IV), and norpestaphthalide A (V) are isolated from Pestalotiopsis clavispora.